Comparison of kinematics on 30 m sprints with 0, 10, 20, 30 and 40% body weight of active resistance in experienced sprinters - van den Tillaar, R. (ISBS Proceedings Archive (Michigan), 2019)
The purpose of this study was to compare kinematics of un-resisted and active resisted 30m sprints with different loads in experienced sprinters. kinematics were measured using laser gun, contact mat and IMUs integrated with a 3-axis gyroscope in fourteen participants during an un-resisted 30 m sprint and sprints with a 10, 20, 30 and 40% of body weight (BW) active resistance. The main findings were that 30m times increased with resp. 16, 31, 51 and 77% from 3.95±0.28 (un-resisted) to 6.99 ±0.85 s (40% BW resistance). These increases were caused by lower maximal velocity reached earlier in the 30m sprints. The lower maximal velocity was a result of shorter step length, flight time and longer contact times. These changes were accompanied with lower maximal knee and hip extension, and plantar flexion velocities with increasing resistance.